Productivity and chemical composition of pearl millet (Pennisetum glaucum) as response to NPK fertilization and biofertilizer - Alonso, Jatnel; Sampaio, R. A.; Colen, F.; Santos, L. D. T.; Fernandes, L. A.; Rocha Junior, V. R.; Nascimento, A. L.; Zuba junior, G. R.; da Cruz, L. R.; Rodrigues, M. E. S. (Cuban Journal of Agricultural Science, 2012)
An experiment was carried out at the rural community ?Las Canoas? from the municipality Montes Claros, Minas Gerais to evaluate the productivity and chemical composition of the pearl millet (Pennisetum glaucum), variety ADR 500 as response to NPK fertilization and biofertilizer. A completely randomized design with three replications and an additional treatment with mineral fertilization were applied. Dosages used were 0, 81.2, 161.2, 202.4 and 245.6 m3 ha-1 for the biofertilizer, 200 kg ha-1 of the complete formula and l50 kg-1 of urea in the chemical treatment. The chemical properties of the soil, the nutrient levels in the foliar biomass and the productivity of the pearl millet were determined. There were no differences between fertilization methods for the pearl millet productivity and the chemical composition of the soil. Only the relationship H + AL was higher (P < 0.05) in the chemical fertilization. Nutrient concentration in the plant was lower for P (0.53 dag kg-1) and K (1.03 dag kg-1) with mineral fertilization. The productivity of the pearl millet, the OM soil content, the ammonia nitrogen (N-NH4+) and the total mineral N augmented with increasing dosages of biofertilizer. Maximum values of fresh matter (25.49 t ha-1) and DM (5.31 t ha-1) were reached with dosages of 120.19 and 134.64 m3 ha-1, respectively. The application of 64.39 m3 h-1 of biofertilizer showed the highest OM content in the soil (3.42 dag kg-1). There was a linear increase for N-NH4+ (83.00 mg dm-3) and total mineral N (141.28 mgdm-3). The increasing application of biofertilizer reduced linearly the percentage of mineral material (MM) and ADF, besides improving the quality of the pearl millet for animal feeding. This strategy favored the P, K and Ca content of the pearl millet biomass. It is recommended under the conditions of this experiment to apply the dosage of 134.64 m3 ha-1 of biofertilizer for obtaining the maximum productivity of dry biomass in pearl millet. Key words: forages, fertilization, pearl millet